SOCIAL INTEGRATION AND RELIGIOUS SPIRITUALITY: The Case of Tharîqah Khalwatiyah Samman in Maros Regency - Sabiq, Muhammad; Arisnawawi, Arisnawawi (State Islamic University North Sumatra, 2025)
This study explores how the tharîqah khalwatiyah samman integrates social, spiritual, and religious life amid the pressures of modernity, which often promote individualism and weaken communal ties. Using a qualitative phenomenological approach, the research examines the experiences of the mursyid, khalîfahs, and members, supported by observations of rituals and community activities. Findings show that integration unfolds on three levels. Spiritually, collective dzikr, wirid, and Qur’anic recitation cultivate inner awareness and a shared sense of devotion. Socially, gotong royong, community service, and mutual support strengthen solidarity and cohesion. Institutionally, the tarekat extends its influence through education, charity, and moral guidance, allowing its values to reach the broader community. Interpreted through Talcott Parsons’ structural functionalism, the order operates as an adaptive system that maintains core values while fostering social harmony. Overall, the tharîqah khalwatiyah samman exemplifies a living synthesis of Sufi spirituality and communal ethics in contemporary Indonesian Islam.